CAR-macrophage: Breaking new ground in cellular immunotherapy - Huang, Ting; Bei, Chenqi; Hu, Zhenhua; Li, Yuanyuan (Frontiers in Cell and Developmental Biology, 2024)
Chimeric Antigen Receptor (CAR) technology has revolutionized cellular immunotherapy, particularly with the success of CAR-T cells in treating hematologic malignancies. However, CAR-T cells have the limited efficacy of against solid tumors. To address these limitations, CAR-macrophages (CAR-Ms) leverage the innate properties of macrophages with the specificity and potency of CAR technology, offering a novel and promising approach to cancer immunotherapy. Preclinical studies have shown that CAR-Ms can effectively target and destroy tumor cells, even within challenging microenvironments, by exhibiting direct cytotoxicity and enhancing the recruitment and activation of other immune cells. Additionally, the favorable safety profile of macrophages and their persistence within solid tumors position CAR-Ms as potentially safer and more durable therapeutic options compared to CAR-T cells. This review explores recent advancements in CAR-Ms technology, including engineering strategies to optimize their anti-tumor efficacy and preclinical evidence supporting their use. We also discuss the challenges and future directions in developing CAR-Ms therapies, emphasizing their potential to revolutionize cellular immunotherapy. By harnessing the unique properties of macrophages, CAR-Ms offer a groundbreaking approach to overcoming the current limitations of CAR-T cell therapies, paving the way for more effective and sustainable cancer treatments..